2020
DOI: 10.1080/19476337.2020.1842502
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and expression of virulence genes in potentially pathogenic bacteria isolated from seafood in Thailand

Abstract: Since seafood can be a reservoir for diverse pathogenic bacteria, the risk to human health associated with seafood merits evaluation. The potentially pathogenic bacteria were isolated from seafood in Thailand. The 40 obtained strains were distinguished by ERIC-PCR fingerprints and identified to the species level by the VITEK 2 system. Their 16S rRNA gene had 97.74-99.79% nucleotide sequence identities to those of bacteria in 11 genera including Aeromonas, Citrobacter,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The presumptive enterobacterial strains were distinguished by ERIC-PCR which has been found to be extremely sensitive and can detect minor differences among strains of the same bacterial genus and species [ 29 ]. The UPGMA dendrogram ( Figure S1 ) constructed from ERIC-PCR fingerprints presents a high level of diversity among 113 strains as showing 20% similarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presumptive enterobacterial strains were distinguished by ERIC-PCR which has been found to be extremely sensitive and can detect minor differences among strains of the same bacterial genus and species [ 29 ]. The UPGMA dendrogram ( Figure S1 ) constructed from ERIC-PCR fingerprints presents a high level of diversity among 113 strains as showing 20% similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Virulence genes can be classified into three types including (1) true virulence genes which encode factors or enzymes producing factors that are involved in bacteria-host interaction and directly cause the pathological damage during infection; (2) virulence-associated genes which encode factors or enzymes producing factors that control virulence gene expression or stimulate virulence factors or are essential for the activity of true virulence factors; and (3) virulence life-style genes which encode factors or enzymes producing factors that promote host colonization or enable evasion of the host immune system or enable interaction survival or employ host-factors for the advantages of survival [ 27 ]. Previous reports demonstrated that the expression of virulence genes was affected by several factors such as (1) nutrient starvation [ 28 , 29 , 30 ]; (2) osmotic agents (NaCl, sucrose, and glucose) [ 29 , 31 , 32 , 33 , 34 , 35 , 36 ]; (3) oxygen [ 37 ]; (4) temperature [ 31 , 38 ]; (5) growth phase [ 29 , 39 , 40 ]; (6) kind of carbon source [ 41 , 42 ]; (7) pH [ 43 ]; (8) sodium glycocholate [ 44 ]; and (9) L-glutamine [ 45 ]. Besides being a major problem in public health concern, enterobacteria are also highlighted for their application potential.…”
Section: Introductionmentioning
confidence: 99%